Differential Diagnosis of MutYH-Associated Polyposis from Sporadic Colon Polyps - A. S. Tsukanov; V. P. Shubin; A. M. Kuzminov; M. Kh. Toboeva; T. A. Savelyeva; V. N. Kashnikov; Yu. A. Shelygin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. In this research, we aim to develop a criterion for differentiating MutYH-associated polyposis from sporadic colon polyps.Materials and methods. A search for mutations in the MutYH gene was carried out using the PCR, electrophoresis and direct sequencing methods among the following groups of people: 18 patients under 45 years old with more than 100 polyps diagnosed in the large intestine; 86 patients over 45 years old with 4–100 polyps; 150 people of the control group.Results. Mutations in the MutYH gene were detected in 2 out of 18 patients having more than 100 polyps. Among 86 patients with 4–100 polyps, mutations were found in 10 people having more than 20 polyps. Mutations in the MutYH gene were not detected in patients with 4–19 polyps (p <0.05). The pathogenic significance of the disease development was established not only for biallelic, but also for monoallelic mutations.Conclusion. For the first time, the lower limit of the polyp number has been established, allowing the MutYH-associated polyposis to be differentiated from sporadic polyps.